2010
DOI: 10.1111/j.1365-2567.2010.03296.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance P primes lipoteichoic acid‐ and Pam3CysSerLys4‐mediated activation of human mast cells by up‐regulating Toll‐like receptor 2

Abstract: Summary Substance P (SP) is a neuropeptide with neuroimmunoregulatory activity that may play a role in susceptibility to infection. Human mast cells, which are important in innate immune responses, were analysed for their responses to pathogen‐associated molecules via Toll‐like receptors (TLRs) in the presence of SP. Human cultured mast cells (LAD2) were activated by SP and TLR ligands including lipopolysaccharide (LPS), Pam3CysSerLys4 (Pam3CSK4) and lipoteichoic acid (LTA), and mast cell leukotriene and chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 40 publications
(48 reference statements)
5
46
0
Order By: Relevance
“…Synergistic release of IL-8 and TNF-a through upregulation of TLR2 expression was observed in a previous study where LAD2 cells were pre-incubated with SP for 24 h prior to being challenged with lipoteichoic acid or Pam3CSK4 (23). In contrast, our data showed that the two commonly employed TLR2 agonists, PGN and Pam3CSK4, differentially modulated SP-induced human mast cell activation via distinct mechanisms when the cells were challenged with SP together or after 24-h pre-incubation with the TLR2 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic release of IL-8 and TNF-a through upregulation of TLR2 expression was observed in a previous study where LAD2 cells were pre-incubated with SP for 24 h prior to being challenged with lipoteichoic acid or Pam3CSK4 (23). In contrast, our data showed that the two commonly employed TLR2 agonists, PGN and Pam3CSK4, differentially modulated SP-induced human mast cell activation via distinct mechanisms when the cells were challenged with SP together or after 24-h pre-incubation with the TLR2 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…As TLR-3 and TLR-7 recognize viral RNA sequences, these results suggest GM-CSF may have a role in enhancing mast cell responses to viral infection. Substance P primes mast cells by up-regulating TLR-2 expression and potentiating associated downstream signalling pathways [77]. Interestingly, substance Pimmunoreactive nerve fibers were reported to be more prevalent in rectosigmoid biopsies from IBS subjects and associated with low-grade inflammation, compared to controls, therefore neuronal responses may modulate innate immunity in IBS [78].…”
Section: Toll-like Receptors and Mast Cells In Ibsmentioning
confidence: 98%
“…SP is known to provide a positive feedback on MCs by causing degranulation and the release of pro-inflammatory mediators that, in turn, can attract other inflammatory cells [31][32][33].…”
Section: Mast Cells In Ems: a Painful Liaison?mentioning
confidence: 99%